(untitled) (MAUSAM, 1993)
Digital records of seismic waves observed at Seismic Research Observatory, Cheng Mai. Thailand have been analysed for two earthquakes in western Nepal. Digital data are processed by the floating filter and phase equalization methods to obtain surface waves free from noise. Group velocities of Love and Rayleigh waves are obtained by frequency time analysis of these noise free surface waves. The period of group velocities ranges from 17 to 62 sec for fundamental mode Rayleigh waves and from 17 to 66 sec for fundamental mode Love waves. The wave paths cross both central Myanmar (Burma) and the Indo-Gangetic plain. The group velocity data of surface waves across central Myanmar (Burma) have been obtained after correction of the data for the path across the Indo-Gangetic plain. Inversion of data gives the average crustal and subcrustal structure of central Myanmar (Burma). The modelled structure shows two separate sedimentary layers each of 8 km thick, The lower sedimentary layer forms the low velocity zone of the crust. The total thickness of central Myanmar (Burma) crust is found to be 55 km